TOURIST ATTRACTIONS AND POSSIBILITIES OF SENTOB VILLAGE IN NAVOI REGION - Rakhimov Sardor Olimovich (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article describes the touristic potential and opportunities of the village of Sentob, Navoi region